A Case of Plasmodium malariae in Bangladesh: A Representation of the Suboptimal Performance of Rapid Diagnostic Approaches in Malaria Elimination Settings - Fatema Tuj Johora; Mohammad Golam Kibria; Hans-Peter Fuehrer; Mohammad Shafiul Alam (Pathogens, 2022)
Plasmodium malariae is a neglected human malaria parasite with low parasitemia that often results in the misdiagnosis and underestimation of the actual disease burden of this pathogen. Microscopy is the best diagnostic tool, despite the fact that rapid diagnostic tests (RDTs) are the best surveillance tool for malaria diagnosis in many rural areas for their ease of use in elimination settings. For parasite antigen detection other than P. falciparum, RDTs depend on essential glycolytic Plasmodium proteins, i.e., Plasmodium lactate dehydrogenase (pLDH) and Plasmodium aldolase (pAldo) antigens. There is a lack of species-specific test kits for P. malariae, and overall, its rapid antigenic test accuracy is questionable. False negative results can accelerate the burden of asymptomatic malaria infection and transmission. Here, we report a case of a malaria patient in Bangladesh infected with P. malariae who tested negative on pLDH and pAldo based RDTs. This case provides useful information for health providers to be aware of possible RDT failure and also for the future development of analytically sensitive test kits for P. malariae.